Kebijakan Kawasan Tanpa Rokok Kota Banda Aceh: Pemetaan Agenda Penelitian - Rezeki Amalia (Puslatbang KHAN, 2018)
The Non-Smoking Area Policy (KTR) in Banda Aceh City requires further studies in order to improve the effectiveness of the policy. Further studies help the implementation more smoothly and higher impact. Therefore, this study aims to map the need for further studies after the enactment of the Non-Smoking Area policy in Banda Aceh City. The result is based on literature review and mapping of issues. It indicates that there are at least three research agendas needed. One of them is a study on the prevalence of juvenile smokers after the Regulation. Increasing the prevalence of juvenile smokers shows that KTR has not been able to avoid youth from the dangers of smoking. In addition, research on the impact of KTR on regional income is also important to study. Concerns about a decline in advertising revenue from cigarette advertising have led to the seriousness of reduced local governments to fully implement cigarette promotion policies. The last issue that needs immediate research is the impact of smoking on poverty. The consumption pattern of people who are dominated by cigarettes causes smoking activities to cause an increase in poverty in Banda Aceh City. This study is important in order to optimize the KTR policy in reducing poverty in Banda Aceh City.